The Influence of Trauma on Autobiographical Memory in the Assessment of Somatoform Disorders According to DSM IV Criteria - Ciaramella, Antonella (Psychiatric quarterly, 2018)
Recalling an event impairs an individual’s later ability to recall related knowledge. Impairment in this retrieval-induced forgetting (RIF) produces a dysfunction in autobiographical memory. This, like somatic symptoms, has been documented in trauma and sexual abuse survivors. To investigate the relationship between past trauma and somatoform disorders, and the role of memory recall dysfunction in this relationship, three sex-matched groups were constituted using DSM IV criteria: Somatoform (SD) (n. 22) other Psychiatric Disorders (PD) (n. 26) and Healthy Subjects (HS) (n. 35). Responses to Stressful Life Events Screening Questionnaire revised (SLESQ-R); Direct Forgetting paradigm (DF) for autobiographical memory; Deese-Roediger-McDermott (DRM) paradigm for false memory; Stanford Scale type A for Post-Hypnotic Amnesia (PHA); Stroop Colour Word test and a digit-span for cognitive assessment; and Somatosensory Amplification Scale (SSAS), Somatic Dissociation Questionnaire (SDQ-20), and Toronto Alexithymia Scale (TAS 20) for somatic discomfort were compared among groups. SSAS, SDQ-20 and TAS F1 were correlated with SLESQ-R scores; subjects with higher numbers of traumatic events (NSE) showed greater capacity to remember items-to-be-forgotten (DFF) and higher SDQ-20 scores. Although the SD group showed higher NSE, their autobiographical memory scores were no different to those of other DSM-IV groups. The somatic-trauma-autobiographical memory impairment relationship is identified by DSM V but not DSM IV criteria for somatoform disorder. Higher NSE appears to correlate with both the presence of somatic discomfort and impaired autobiographical memory, suggesting autonoetic consciousness dysfunction in subjects with past trauma and current somatic symptom disorders.